Politics in the Commonwealth Caribbean. - Sutton, Paul (1991)
Argues that the political process in post-colonial Commonwealth Caribbean continued to be based on acceptance rather than reflection of the Westminster-Whitehall system. The political configuration thus constituted bestows a distinctive identity on its member states which set them apart from their neighbours in the region and the rest of Latin America.